Acromelic frontonasal dysostosis and ZSWIM6 mutation: phenotypic spectrum and mosaicism. Issue 3 (3rd February 2016) - Twigg, S.R.F.; Ousager, L.B.; Miller, K.A.; Zhou, Y.; Elalaoui, S.C.; Sefiani, A.; Bak, G.S; Hove, H.; Hansen, L.K.; Fagerberg, C.R.; Tajir, M.; Wilkie, A.O.M.
Abstract : Acromelic frontonasal dysostosis (AFND) is a distinctive and rare frontonasal malformation that presents in combination with brain and limb abnormalities. A single recurrent heterozygous missense substitution in ZSWIM6, encoding a protein of unknown function, was previously shown to underlie this disorder in four unrelated cases. Here we describe four additional individuals from three families, comprising two sporadic subjects (one of whom had no limb malformation) and a mildly affected female with a severely affected son. In the latter family we demonstrate parental mosaicism through deep sequencing of DNA isolated from a variety of tissues, which each contain different levels of mutation. This has important implications for genetic counselling. Abstract :